A qualitative study of governance of evolving response to non-communicable diseases in low-and middle- income countries: current status, risks and options - Rani Manju; Nusrat Sharmin; Hawken Laura H (BMC, 2012)
Abstract Background Segmented service delivery with consequent inefficiencies in health systems was one of the main concerns raised during scaling up of disease-specific programs in the last two decades. The organized response to NCD is in infancy in most LMICs with little evidence on how the response is evolving in terms of institutional arrangements and policy development processes. Methods Drawing on qualitative review of policy and program documents from five LMICs and data from global key-informant surveys conducted in 2004 and 2010, we examine current status of governance of response to NCDs at national level along three dimensions- institutional arrangements for stewardship and program management and implementation; policies/plans; and multisectoral coordination and partnerships. Results Several positive trends were noted in the organization and governance of response to NCDs: shift from specific NCD-based programs to integrated NCD programs, increasing inclusion of NCDs in sector-wide health plans, and establishment of high-level multisectoral coordination mechanisms. Several areas of concern were identified. The evolving NCD-specific institutional structures are being treated as 'program management and implementation' entities rather than as lead 'technical advisory' bodies, with unclear division of roles and responsibilities between NCD-specific and sector-wide structures. NCD-specific and sector-wide plans are poorly aligned and lack prioritization, costing, and appropriate targets. Finally, the effectiveness of existing multisectoral coordination mechanisms remains questionable. Conclusions The 'technical functions' and 'implementation and management functions' should be clearly separated between NCD-specific units and sector-wide institutional structures to avoid duplicative segmented service delivery systems. Institutional capacity building efforts for NCDs should target both NCD-specific units (for building technical and analytical capacity) and sector-wide organizational units (for building program management and implementation capacity) in MOH. The sector-wide health plans should reflect NCDs in proportion to their public health importance. NCD specific plans should be developed in close consultation with sector-wide health- and non-health stakeholders. These plans should expand on the directions provided by sector-wide health plans specifying strategically prioritized, fully costed activities, and realistic quantifiable targets for NCD control linked with sector-wide expenditure framework. Multisectoral coordination mechanisms need to be strengthened with optimal decision-making powers and resource commitment and monitoring of their outputs.